KI 2009 advances in artificial intelligence : 32nd Annual German Conference on AI, Paderborn, Germany, September 15-18, 2009 : proceedings - German Conference on Artificial Intelligence (Lecture notes in computer science, 2009)
This book constitutes the thoroughly refereed proceedings of the 32nd Annual German Conference on Artificial Intelligence, KI 2009, held in Paderborn, Germany, in September 2009. The 76 revised full papers presented together with 15 posters were carefully reviewed and selected from 126 submissions. The papers are divided in topical sections on planning and scheduling; vision and perception; machine learning and data mining; evolutionary computing; natural language processing; knowledge representation and reasoning; cognition; history and philosophical foundations; AI and engineering; automated reasoning; spatial and temporal reasoning; agents and intelligent virtual environments; experience adn knowledge management; and robotics. Planning and scheduling -- Vision and perception -- Machine learning and data mining -- Evolutionary computation -- Natural language processing -- Knowledge representation and reasoning -- Cognition -- History and philosophical foundations -- AI and engineering -- Automated reasoning -- Spatial and temporal reasoning -- Agents and intelligent virtual environments -- Experience and knowledge management -- Robotics -- Posters.